2019
DOI: 10.1177/0886260519835002
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Distress Tolerance in the Relationship Between Childhood Maltreatment and Mental Health Outcomes Among University Students

Abstract: A wealth of empirical literature has documented that the experience of childhood maltreatment is related to an increased risk for the development of psychopathologies in adulthood. Empirical studies examining the factors that could possibly explain this relationship, however, remain sparse. The emerging literature on Distress Tolerance suggests that it could possibly act as an explanatory or mediating factor within this relationship. The current study therefore examined the mediating role of Distress Tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 71 publications
(107 reference statements)
4
14
0
1
Order By: Relevance
“…As excepted, this study found that stressful life events were positively related with suicide risk. This nding was in line in with previous studies [12,17]. The result showed that distress tolerance was negatively related with depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As excepted, this study found that stressful life events were positively related with suicide risk. This nding was in line in with previous studies [12,17]. The result showed that distress tolerance was negatively related with depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of stressful experiences on mental heath outcomes were in uenced by the ability of individuals to endure distress. Individuals with low levels of distress tolerance is associated with increased severity of depressive symptoms [16,17]. Besides, distress tolerance is considered as a promising target within a variety of psychotherapeutic approaches in the context of treatments for depression [18].…”
Section: Introductionmentioning
confidence: 99%
“…Punishment by incarceration may further aggravate the psychological trauma of CSA victims, so providing appropriate cognitive, behavioral and family treatment is beneficial (Kozak et al, 2018). Furthermore, assessment of PA should be incorporated into initial clinical assessments of adolescents with a CSA background to establish the risk of developing offending behavior (Robinson et al, 2021). Finally, college campuses should emphasize the role of education engagement, establish related courses to educate and enhance the PA of students, and maintain close contact with students’ families to provide necessary social support (Lo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, exposure to nature may regulate stress, thus enhancing tolerance to negative emotions ( 34 , 35 ), which may further reduce the risk of depression and anxiety ( 36 , 37 ). Based on the similar benefits observed in direct and indirect nature exposure, it is reasonable to hypothesize that nature exposure through windows may also facilitate prisoners' mental health by reducing their sense of loneliness as well as enhancing distress tolerance.…”
Section: Conceptual Framework Of Exposure-response Pathwaysmentioning
confidence: 99%